Effects of sulforaphane and its S- and R-enantiomers on the expression and activities of human drug-metabolizing cytochromes P450. (April 2015) - Srovnalova, Alzbeta; Vanduchova, Alena; Svecarova, Michaela; Anzenbacherova, Eva; Tomankova, Veronika; Anzenbacher, Pavel; Dvorak, Zdenek
Highlights: Sulforaphane is a chiral isothiocyanate occurring in cruciferous vegetables. Sulforaphane exerted insignificant effects on the expression of P450s. Sulforaphane was dose-dependently cytotoxic in human cell lines. Sulforaphane did not affect the expression and activity of PXR, AhR and GR. Sulforaphane inhibited CYP2A6, CYP2D6 and CYP3A4. Abstract: The effects of S/R-enantiomers of sulforaphane on drug-metabolizing cytochromes P450, in particular: (i) expression of CYP1A1/2, CYP2B6, CYP2C9, CYP3A4 mRNAs and proteins in human hepatocytes; (ii) mRNA expression and activity of pregnane X receptor (PXR), aryl hydrocarbon receptor (AhR) and glucocorticoid receptor (GR) in human hepatocytes and transgenic gene reporter cell lines, respectively; (iii) catalytic activity of CYP1A2, CYP2A6, CYP2B6, CYP2C8, CYP2C9, CYP2C19, CYP2D6, CYP2E1 and CYP3A4 in human liver microsomes and human hepatocytes were investigated. The major findings are that (i) sulforaphane exerted insignificant effects on the expression of CYP1A1/2, CYP2B6, CYP2C9, CYP3A4 mRNAs and proteins. We observed induction of CYP2C9 and CYP2B6, but these effects were inconsistent, not enantiospecific, with inter-individual variability between human hepatocytes cultures; (ii) sulforaphane displayed a dose-dependent but not enantiospecific cytotoxicity in HepG2, HeLa and LS174T cells. Sulforaphane had no effects on the expression (mRNA) and transcriptional activity (agonist/antagonist) of AhR, GR and PXR as revealed by RT-PCR and gene reporter assays; (iii) sulforaphane inhibited CYP2A6 (IC50 12 µM), CYP2D6 (IC50 39 µM) and CYP3A4 (IC50 52 µM) in hepatocytes; in microsomes, CYP2D6 (Ki 111 µM) CYP3A4 (Ki 27 µM-testosterone or Ki 193 µM-midazolam) were inhibited and the effects were not enantiospecific.